Estudio Retrospectivo Del Porcentaje De Preñez Y Viabilidad De Reabsorción De Embriones En El Criadero La Marqueza Entre 2020 Y 2021 - Otálora Rojas, Kevin Andrés; Pulido Aldana, Juan Esteban; Arévalo Guasca, Edgar Camilo (Universidad Antonio Nariño, 2023)
Embryo transfer is one of the updated techniques currently used throughout the world and which presents an efficiency rate both in the collection of the embryo through washing and the pregnancy rate at the time of carrying out the transfer process. There are multiple reproductive biotechnologies today, where the Veterinary Doctor / Veterinary Doctor and Zootechnician will implement the method where he has obtained the best results.